Multi-classification Network for Detecting Skin Diseases using Deep Learning and XAI - Athina, Fahima Hasan; Sara, Sadaf Ahmed; Tabassum, Nishat; Sarwar, Quazi Sabrina; Jannat Era, Mun Tarin (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.